Effectiveness of in vitro fertilization in women with previous tubal sterilization - Malacova, Eva; Kemp, A.; Hart, R.; Jama-Alol, K.; Preen, D. (Elsevier, 2015)
© 2015 Elsevier Inc. All rights reserved. Objective The objective was to determine the effectiveness of in vitro fertilization (IVF) on live-delivery rates in women who had previously undergone tubal sterilization. Study design We examined first IVF live deliveries for women aged 20-44 years at their first embryo transfer (ET) with history of hospital admission for tubal sterilization in Western Australia (WA). The ET cycles (n = 178) were ascertained over the period of 1996 to 2010 using WA hospital records. A control group of subfertile women matched by age was randomly selected (n = 178). We used Kaplan-Meier curves and life-table analysis to evaluate the cumulative live-delivery rates. Results An overall cumulative live-delivery rate in women who had undergone previous tubal sterilization (31%) was comparable to that of subfertile controls (34%) within the first 24 months. Younger women (aged 20-34 years) with previous sterilization (34%) were slightly more likely to deliver an IVF live baby than older women (aged 35-39 and 40-44 years) (33% and 22%, respectively), although this difference was not statistically significant (p =.449). Conclusion Women who desire fertility after a tubal sterilization procedure and undergo IVF have rates of pregnancy similar to age-matched subfertile IVF control patients. Implications In vitro fertilization success in women who had undergone previous tubal sterilization is similar to that of the subfertile controls and thus does not depend on past fertility. Age is the most important predictive factor in achieving pregnancy.